Audience Reception of Intermediality in Sandiwara Sastra Podcast - Delimaniati Bungsuna Manggala Manggala (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
Intermediality is a commonplace in the literary world, however it has not been widely found in the form of audio podcasts. The use of podcasts as a new medium for distributing audio plays can be an attractive option considering that youth as the target audience are currently very fond of podcasts. The Sandiwara Sastra podcast is interesting to study because it used a popular literary works that already have numerous readers, but it is not easy to make plays in an audio format that are liked by youth who are more familiar with visual literature. The purpose of this study is to determine the youth’s reception of intermediality on the Sandiwara Sastra podcast and to find out the role of the interpretive community in the production of meaning. With Irina O Rajewsky's intermediality framework and Alasuutari's third generation audience reception analysis framework. The results show that the intermediality of the Sandiwara Sastra podcast can provide a new experience for youth as the audience in enjoying literature. The audio component makes the audience feel closer to the literary story because audio can create a theater of mind. Audio can also evoke memories and bring back nostalgia when the audience listens to them. The use of the Sandiwara Sastra podcast also gives the audience a choice regarding the mode of listening to the podcast, even though the audience is not focused on enjoying literature.